Wide‐Bandgap Organic–Inorganic Lead Halide Perovskite Solar Cells. Issue 14 (8th March 2022) - Tong, Yao; Najar, Adel; Wang, Le; Liu, Lu; Du, Minyong; Yang, Jing; Li, Jianxun; Wang, Kai; Liu, Shengzhong (Frank)
Abstract: Under the groundswell of calls for the industrialization of perovskite solar cells (PSCs), wide‐bandgap (>1.7 eV) mixed halide perovskites are equally or more appealing in comparison with typical bandgap perovskites when the former's various potential applications are taken into account. In this review, the progress of wide‐bandgap organic–inorganic hybrid PSCs—concentrating on the compositional space, optimization strategies, and device performance—are summarized and the issues of phase segregation and voltage loss are assessed. Then, the diverse applications of wide‐bandgap PSCs in semitransparent devices, indoor photovoltaics, and various multijunction tandem devices are discussed and their challenges and perspectives are evaluated. Finally, the authors conclude with an outlook for the future development of wide‐bandgap PSCs. Abstract : In this review, the progress of wide‐bandgap organic–inorganic hybrid perovskite solar cells (PSCs) are initially summarized and the issues of phase segregation and voltage loss are assessed. Then, the diverse applications of wide‐bandgap PSCs in semitransparent devices, indoor photovoltaics, and tandem devices are discussed and their challenges and perspectives are evaluated.